Study of the neonatal outcomes in babies born to elderly mothers and young mothers - Santappanavar, Malavika P.; Khan, Habeeb U.; M. D., Jaidev; Hegde, Pavan (International Journal of Contemporary Pediatrics, 2018)
Background: More and more women are focusing on obtaining higher education and reaching career objectives. This has in turn, lead to delayed marriage and child birth at a later age. Advanced maternal age at birth has been found to be associated with preterm delivery, low birth weight, intrauterine fetal death and increased perinatal morbidity and mortality. The aim of our study was to know the neonatal outcome in elderly mothers and young mothers, and to compare the neonatal outcome of these two groups. Methods: Present study was a cross sectional, analytical case control study, done in babies delivered to mothers >35 years and <35 years. Information like period of gestation, birth weight, APGAR at 1 minute and 5 minutes, NICU admissions, neonatal outcome like respiratory distress, jaundice, convulsion, etc. were recorded in a proforma. Collected data was analysed using appropriate statistical tests. Results: In the present study, total sample size was 460 (230 cases and 230 controls). Incidence of preterm deliveries, Low birth weight, NICU admissions were significantly more in case group (babies born to mothers >35 years) than the control group (babies born to mothers between 19 to 35 years). Conclusions: It was observed that low birth weight, prematurity and NICU admissions were more common in babies born to elderly mothers.